Parathyroid hemangioma - Odille Mejia; Hisham F. Bahmad; Kei Shing Oh; Juan C. Paramo; Robert Poppiti (University of São Paulo, 2021)
Background: Hemangiomas are benign neoplasms of capillary proliferation that arise from a developmental anomaly where angioblastic mesenchyme fails to form canals. Most hemangiomas arise in the head and neck region, either superficially in the skin or deeper within endocrine organs such as the parotid gland. Parathyroid hemangiomas, however, are extremely rare, with only five cases previously reported in the literature. Case presentation: Herein, we present a case of a 68-year-old man with a hemangioma almost completely replacing the right upper parathyroid gland, grossly measuring 1.3 × 1.3 × 1.2 cm and weighing 700 mg, associated with primary hyperparathyroidism. Conclusions: Parathyroid gland enlargement due to vascular neoplasms such as hemangiomas can mimic, both clinically and radiographically, hyperplasias and/or adenomas. Surgeons need to be aware of the presence of this entity and should consider it in the differential diagnosis of hyperparathyroidism or parathyroid gland enlargement.